Evolution of Hominin Detoxification: Neanderthal and Modern Human Ah Receptor Respond Similarly to TCDD. (24th November 2020) - Aarts, Jac M M J G; Alink, Gerrit M; Franssen, Henk J; Roebroeks, Wil
Abstract: In studies of hominin adaptations to fire use, the role of the aryl hydrocarbon receptor (AHR) in the evolution of detoxification has been highlighted, including statements that the modern human AHR confers a significantly better capacity to deal with toxic smoke components than the Neanderthal AHR. To evaluate this, we compared the AHR-controlled induction of cytochrome P4501A1 ( CYP1A1 ) mRNA in HeLa human cervix epithelial adenocarcinoma cells transfected with an Altai-Neanderthal or a modern human reference AHR expression construct, and exposed to 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD). We compared the complete AHR mRNA sequences including the untranslated regions (UTRs), maintaining the original codon usage. We observe no significant difference in CYP1A1 induction by TCDD between Neanderthal and modern human AHR, whereas a 150–1, 000 times difference was previously reported in a study of the AHR coding region optimized for mammalian codon usage and expressed in rat cells. Our study exemplifies that expression in a homologous cellular background is of major importance to determine (ancient) protein activity. The Neanderthal and modern human dose–response curves almost coincide, except for a slightly higher extrapolated maximum for the Neanderthal AHR, possibly caused by a 5′-UTR G-variant known from modern humans (rs7796976). Our results are strongly at odds with a major role of the modern human AHR in the evolution of hominin detoxification of smoke components and consistent with our previous study based on 18 relevant genes in addition to AHR, which concluded that efficient detoxification alleles are more dominant in ancient hominins, chimpanzees, and gorillas than in modern humans.